(untitled) (Fiep Bulletin - online, 2014)
People with medullar trauma suffer many deep changes in their lives, and go through an intense period of learning in order to be able to deal with their new characteristics. The changes will determine their new standard of life, so they need a rehabilitation e/or reeducation period for these new factors. Most of the times, because of the paraplegic or the tetraplegy, these people have to use wheel chairs. In order to adapt and have independence they need to aquire certain abilities for their daily lives. The objective of this study is to show the contribution of physical education in the necessary abilities for the independence of the patient with medular trauma; in the teaching of how to use the wheel chair, mobility in the matress and transference; in a transubject team of the Hospital Universitário Getulio Vargas (HUGV), in the period of 2003 to 2006. For that, 32 students with medular trauma were selected, 23 paraplegic and 7 tetraplegic, that were part of Programa de Atividade Motora para Deficientes (PROAMDE) of Universidade Federal do Amazonas (UFAM) The data that were aquired through the evaluations were statisticly analysed, and based on the analysis of the graphics, we got to the result of a 43,76% of complete learning of the Wheel chair (14 students pupils) in the item, 30% (09 students) in transferences and 33,3% (10 students) in mobility.